2007
DOI: 10.1002/pen.20731
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of two nonlinear viscoelastic constitutive relations for polymers under multiaxial loadings

Abstract: Two viscoelastic constitutive relations in differential form are further developed here to include material nonlinearity and distinction between loading and unloading regimes, which is a characteristic of polymers. The effects of hydrostatic pressure and anisotropy in tension and compression on the deformation response of polymers are accounted for through the definition of a pressuredependent equivalent stress. In the uniaxial stress state, these constitutive relations reduce to the two wellknown mechanical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For monotonic and first reversal response, Colak and Dusunceli [7], Colak [8], Bergstrom and Boyce [10], Amida et al [22], Drozdov [34], and Ellyin et al [35] showed good simulations. For subsequent cyclic responses, simulation studies in the literature are extremely limited [5,6].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For monotonic and first reversal response, Colak and Dusunceli [7], Colak [8], Bergstrom and Boyce [10], Amida et al [22], Drozdov [34], and Ellyin et al [35] showed good simulations. For subsequent cyclic responses, simulation studies in the literature are extremely limited [5,6].…”
Section: Introductionmentioning
confidence: 92%
“…They have not simulated the subsequent cyclic responses of the polymeric material. Model development study for cyclic responses of UHMWPE is extremely limited [5,6,35]. Hence, this paper evaluates the VBOP model against simulating both the strain and stress-controlled cyclic responses.…”
Section: Simulation Of Uhmwpe Cyclic Responses By the Vbop Modelmentioning
confidence: 99%
“…For example, Galante used the constitutive equation to describe viscoelastic effects in an integral equation of the K-BKZ type, suitable for polymer solutions and melts [40]. The problem with the constitutive equation of K-BKZ is that it is not fully applicable to predicting the nonlinear rheological behavior of viscoelastic materials [39]- [41].…”
Section: Rheological Modelling Of Viscoelastic Compositesmentioning
confidence: 99%
“…Even in actual publications the model is frequently used to describe the material behavior of polymers (e.g. 8–11).…”
Section: Materials Modelmentioning
confidence: 99%